Treatment of refractory germ-cell tumours with single-agent cabazitaxel: a German testicular cancer study group case series - Oing, Christoph; Hentrich, Marcus; Lorch, Anja; Gläser, Dietrich; Rumpold, Holger; Ochsenreither, Sebastian; Richter, Stephan; Dieing, Annette; Zschäbitz, Stefanie; Pereira, Ronnie Rodrigues; Bokemeyer, Carsten; Seidel, Christoph (Journal of cancer research and clinical oncology, 2020)
Outcomes of multiply relapsed, refractory germ-cell tumour (GCT) patients remain poor with an overall survival (OS) of a few months only. Thus, new therapeutic advances are urgently needed. Cabazitaxel has shown preclinical activity in platinum-resistant GCT models. Here, we report the first clinical case series of cabazitaxel treatment for platinum-refractory GCT.
Published: 14 December 2019
Gesehen am 24.06.2020